2006
DOI: 10.1128/iai.00534-06
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Contributions of Clostridium perfringens Type C Toxins to Lethality in the Mouse Intravenous Injection Model

Abstract: The gram-positive anaerobe Clostridium perfringens produces a large arsenal of toxins that are responsible for histotoxic and enteric infections, including enterotoxemias, in humans and domestic animals. C. perfringens type C isolates, which cause rapidly fatal diseases in domestic animals and enteritis necroticans in humans, contain the genes for alpha toxin (plc), perfringolysin O (pfoA), beta toxin (cpb), and sometimes beta2 toxin (cpb2) and/or enterotoxin (cpe). Due to the economic impact of type C-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(138 citation statements)
references
References 39 publications
8
127
0
3
Order By: Relevance
“…Calculada en forma triplicada para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 4 Capacidad de producción de Cp-PLC y clasificada por actividad lecitinasa: baja (<1 u.a./mL), mediana (1-3 u.a./mL) y alta (>3 u.a./mL) 5 Actividad hemolítica siguiendo lo descrito por Titball et al (1989), expresada en unidades arbitrarias hemolíticas (u.a.h.) por mL y calculada en forma duplicada (A y B) para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 6 Actividad perfringolisina, según la metodología descrita por Fisher et al (2006), expresada en unidades arbitrarias hemolíticas (u.a.h.) por mL y calculada en forma duplicada (A y B) para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 7 Actividad citotóxica evaluada en línea celular HEp-2.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…Calculada en forma triplicada para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 4 Capacidad de producción de Cp-PLC y clasificada por actividad lecitinasa: baja (<1 u.a./mL), mediana (1-3 u.a./mL) y alta (>3 u.a./mL) 5 Actividad hemolítica siguiendo lo descrito por Titball et al (1989), expresada en unidades arbitrarias hemolíticas (u.a.h.) por mL y calculada en forma duplicada (A y B) para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 6 Actividad perfringolisina, según la metodología descrita por Fisher et al (2006), expresada en unidades arbitrarias hemolíticas (u.a.h.) por mL y calculada en forma duplicada (A y B) para cada aislado, obteniéndose la media y la desviación estándar de las medias (SD) 7 Actividad citotóxica evaluada en línea celular HEp-2.…”
Section: Resultados Y Discusiónunclassified
“…Posee gen plc [Cp-PLC]) pero carecen de gen cpb2 (toxina β2) y gen cpe (CPE) 6 Genotipo A β2 +vo . Poseen genes plc [Cp-PLC]) y cpb2 (toxina β2) pero carecen del gen cpe (CPE) la escasa producción de Cp-PLC o la ausencia de hemolisinas tipo Cp-PLC de manera similar a reportes en aislados C. perfringens genotipo C cpb2 +vo (Fisher et al, 2006).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Several other mammalian cells lines, in addition to Caco-2 cells, were able to induce the quick increase in virulent in rabbit ileal loops. This study 7 further determined that, in the presence of TI, purified β-toxin induces hemorrhagic necrosis in rabbit ileal loops. Collectively, these results indicated that β-toxin is necessary and sufficient for the enteric virulence of type C isolate CN3685 in rabbit ileal loops.…”
Section: Clostridium Perfringensmentioning
confidence: 99%
“…7 However, since type C disease involves toxin production in the intestines, we recently examined 11 whether contact with human enterocytelike Caco-2 cells might affect the kinetics of toxin secretion or production by type C isolates.…”
Section: Host Cell Contact Induces a Rapid Upregulation Of Toxin Prodmentioning
confidence: 99%